Product and Packaging Innovation Strategies for Enhancing MSME Competitiveness: A Case Study of Bale Seafood from an Educational Management Perspective - Ifan Maulana; Rian Hardiansyah (Journal of Educational Management Research, 2025)
This study aims to examine the influence of creativity and product innovation on business development and competitiveness in Micro, Small, and Medium Enterprises (MSMEs), using Bale Seafood as a case study. A qualitative descriptive approach was employed, with data collected through in-depth interviews with the business owner and direct field observations. The findings reveal that the owner’s creativity in developing diversified processed seafood products, combined with continuous packaging innovation, significantly contributes to business growth, market expansion, and long-term sustainability. Innovation practices at Bale Seafood extend beyond product improvement to include adaptive learning processes, customer engagement, and community-based knowledge exchange. From an educational management perspective, these practices reflect informal learning, experiential knowledge development, and capacity building within the enterprise. The study implies that strengthening learning-based management, entrepreneurial education, and skill development is essential for enhancing MSME innovation capacity. Support from stakeholders, such as training programs and mentoring, can further facilitate the transfer of knowledge and the adoption of appropriate technology. Overall, integrating educational management principles into innovation strategies can serve as an effective approach to improving MSME competitiveness in dynamic market environments.